Biomass and Nutrient Accumulation by Dual-Purpose Hemp and Concurrent Soil Profile Water Depletion at Manhattan, KS, in 2021 - Kraig Roozeboom; Jason Griffin; Lucas Haag; Gerard Kluitenberg; Dorivar Ruiz Diaz; Michael Shelton; Tami Myers; Clint Wilson; Andrew Euler; Ike Bahr; Brian Owuoche (Kansas Agricultural Experiment Station Research Reports, 2023)
Hemp has garnered interest as a potential crop that is not constrained by the typical food, feed, and fuel market channels. Although hemp varieties are available for the production of either grain, fiber, or both (dual-purpose: both grain and fiber) markets, little research-based information is available on hemp growth and water use in Kansas environments. In 2019, Kansas State University researchers began conducting experiments to characterize hemp growth, nutrient uptake, and soil water depletion at three locations representing the precipitation gradient across Kansas. In 2021, one fiber and one grain variety were evaluated with and without fertilizer nitrogen. Soil water content and biomass accumulation were monitored in plots with full nitrogen fertilizer. Multiple plantings of the experiment at Haysville had to be abandoned because heavy rains soon after planting prevented successful stand establishment. The Colby experiment was abandoned because dry soils prevented successful stand establishment. Results from the experiment at Manhattan confirmed the benefit of nitrogen fertilizer, which roughly doubled total biomass yield. Although total biomass yield was similar for the two varieties, more of that yield was partitioned to grain in the grain variety, and stalks in the fiber variety. Nutrient uptake patterns were similar to those observed the previous year, with nitrogen and potassium accumulation occurring at a faster rate than dry matter, and phosphorus accumulation lagging that of dry matter. Carbon accumulation closely followed total dry matter accumulation. Hemp appeared to extract soil water to a depth of 5 feet because soil water content did not change at deeper depths. The sum of net depletion of the soil profile water plus precipitation was 14.64 inches, but some of the precipitation came in intense events causing a portion to run off. As an indeterminate species, hemp continues vegetative growth after flowering begins, increasing the probability that some grain will be produced even when resources are limited. Across three experiments conducted in Kansas in 2020 and 2021, stalk yields have varied by a factor of 1.5, and grain yields by a factor of 13.3. Relatively stable stalk yield coupled with more variable grain yield reveals hemp’s potential ability to adjust growth to match the inconsistent growing conditions typical of Kansas.
Keywords: hemp; biomass; nutrients; soil water